Analysis of the implementation of guidance and counseling supervision at state senior high schools of Singkawang city - Abd. Basith; Slamat Fitriyadi (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
The objectives of this research are: (1) to describe and analyze the implementation of guidance and counseling supervision at the State Senior High Schools of Singkawang City, and (2) to find main factors inhibiting the implementation of guidance and counseling supervisory at the State Senior High Schools of Singkawang City. The results show that: (1) the implementation of the guidance and counseling supervision has still many weaknesses on each stage done by the supervisors, such as unidentified guidance and counseling teachers‘ needs, the program planning is not yet organized well, the supervisors do not use particular approaches, and they do not control the supervisions carried out, (2) some factors inhibiting the implementation of guidance and counseling supervision include lack of guidance and counseling supervision forces that so many guidance and counseling teachers are not supervised optimally, lack of knowledge and understanding by the supervisors on the implementation of the guidance and counseling supervision, and also minimal development of supervisory competencies in the guidance and counseling field.